Iron-based superconductors: magnetism, superconductivity and electronic structure (Review Article) - Kordyuk, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Angle resolved photoemission spectroscopy (ARPES) reveals the features of the electronic structure of quasitwo-dimensional crystals, which are crucial for the formation of spin and charge ordering and determine the mechanismsof electron–electron interaction, including the superconducting pairing. The newly discovered ironbasedsuperconductors (FeSC) promise interesting physics that stems, on one hand, from a coexistence of superconductivityand magnetism and, on the other hand, from complex multi-band electronic structure. In this reviewI want to give a simple introduction to the FeSC physics, and to advocate an opinion that all the complexity ofFeSC properties is encapsulated in their electronic structure. For many compounds, this structure was determinedin numerous ARPES experiments and agrees reasonably well with the results of band structure calculations.Nevertheless, the existing small differences may help to understand the mechanisms of the magnetic orderingand superconducting pairing in FeSC.